The variation of Temperature and Pressing Time on Particle Board Quality from Waste Oil Palm Trunk Using Phenol Formaldehyde Adhesive - Syahroni Hasan Siregar; Rudi Hartono; Tito Sucipto; Apri Heri Iswanto (Peronema Forestry Science Journal, 2014)
The waste of oil palm trunks could be used as raw material for particle boards. The purpose of these studies were to known the physical, mechanical properties and to know durability of particleboard on termites attack. The variation of treatment were temperature (160, 170 and 180 °C) and pressing time (5, 7, 8 and 11 minutes). Particleboards were made from waste of oil palm trunk using phenol formaldehyde of 8 % with size 30 cm x 30 cm x 1 cm and density target of 0.70 gr/cm3. Particleboard were tested physical and mechanical properties and will be compared by SNI 03-2105-2006. Also, it will be tested by grave yard test along 100 days for durability from termites attack.Result showed that density, moisture content, water absorption, thickness swelling, MOE, MOR and Internal bond were 0.65 -0.77 g/cm³, 4.89-7.76 %, 57.36-71.53 %, 7.03-13.28 %, 10.595 -19.258 kg/cm², 57.67 -135.55 kg/cm², 1.67-3.81 kg/cm², respectively. All of density, moisture content and internal bond fulfilled standard. The other hand all of MOE didn’t fulfilled the standard. While thickness swelling and MOR only several which fulfilled the standard. Weight loss particleboard from subterranean termites were 32.33-87.45 %. Particleboard durability was classified as very bad. The best treatment of particleboard was attained by pressing temperature of 160°C for 7 minutes.Key words: oil palm trunk, particleboard, temperature and pressing time, phenol formaldehida